2017
DOI: 10.1002/jcb.26377
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain attenuates the oxidative stress induced by lipopolysaccharides in the cerebellum of rats

Abstract: Our study aimed to analyze the effect of ouabain administration on lipopolysaccharide (LPS)-induced changes in oxidative parameters, membrane lipid composition, and the activities of some important enzymes of the nervous system. The content of phospholipids, cholesterol, and gangliosides were analyzed in Wistar rats after intraperitoneal injection of ouabain (1.8 μg/kg), LPS (200 μg/kg), or saline. Oxidative parameters were also evaluated, including the activities of superoxide dismutase, catalase and glutathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 57 publications
7
29
0
6
Order By: Relevance
“…In our study LPS was able to induce a hypoccampal oxidative stress, demonstrated by the increase of lipid peroxidation and the decrease of GSH (Figure A and B, respectively). In agreements with previous studies showing that LPS caused an increase in lipid peroxidation and a decrease in GSH content in the hippocampus of Swiss mice, hippocampus of newborn rats and in cerebellum of rats . Moreover, Figure C corroborate data by Barreiro et al, who demonstrated increase of carbonylated protein in Sprague Dawley rats after LPS administration.…”
Section: Discussionsupporting
confidence: 92%
“…In our study LPS was able to induce a hypoccampal oxidative stress, demonstrated by the increase of lipid peroxidation and the decrease of GSH (Figure A and B, respectively). In agreements with previous studies showing that LPS caused an increase in lipid peroxidation and a decrease in GSH content in the hippocampus of Swiss mice, hippocampus of newborn rats and in cerebellum of rats . Moreover, Figure C corroborate data by Barreiro et al, who demonstrated increase of carbonylated protein in Sprague Dawley rats after LPS administration.…”
Section: Discussionsupporting
confidence: 92%
“…2) Inhibiting Na pumps may accelerate the loss of ion gradients, thus enhancing edema formation. These contrasting CTS effects have been previously described in the CNS (34)(35)(36)(37) but are beyond the scope of the present study.…”
Section: Discussionsupporting
confidence: 54%
“…Notably, depletion of membrane cholesterol resulted in the displacement of claudin-3, -4, -7 and occludin from the cholesterol rich domains associated with TJs, while claudin-1 was unaffected [ 52 ]. Intriguingly, a neuroprotective effect of ouabain against LPS-induced oxidative stress in rat cerebellum involves promoting membrane lipid remodeling [ 53 ]. Further studies are necessary to testify features of the Na,K-ATPase/claudin-1 functional interaction and to identify their precise molecular basis.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in primary culture of rat cortical neurons that ouabain at sub-nanomolar concentrations can prevent Ca 2+ overload and neuronal apoptosis in excitotoxic stress [ 62 ]. The same doses of chronically administrated ouabain used in this study (1 µg/kg–1.8 µg/kg) significantly improves mouse recovery following traumatic brain injury [ 63 ] and attenuates the oxidative stress induced by LPS in rat cerebellum [ 53 ]. The role of ouabain in inflammatory processes in the central nervous system is reviewed elsewhere [ 64 ].…”
Section: Discussionmentioning
confidence: 99%